Mistreatment during childbirth and postnatal period reported by women in Nepal -a multicentric prevalence study - Rejina Gurung; Md Moinuddin; Avinash K. Sunny; Amit Bhandari; Anna Axelin; Ashish KC (BMC, 2022)
Abstract Introduction Trust of women and families toward health institutions has led to increased use of their services for childbirth. Whilst unpleasant experience of care during childbirth will halt this achievement and have adverse consequences. We examined the experience of women regarding the care received during childbirth in health institutions in Nepal. Method A prospective cohort study conducted in 11 hospitals in Nepal for a period of 18 months. Using a semi-structured questionnaire based on the typology of mistreatment during childbirth, information on childbirth experience was gathered from women (n = 62,926) at the time of discharge. Using those variables, principal component analysis was conducted to create a single mistreatment index. Bivariate and multivariate linear regression analyses were conducted to assess the association of the mistreatment index with sociodemographic, obstetric and newborn characteristics. Result A total of 62,926 women were consented and enrolled in the study. Of those women, 84.3% had no opportunity to discuss any concerns, 80.4% were not adequately informed before providing care, and 1.5% of them were refused for care due to inability to pay. According to multivariate regression analysis, women 35 years or older (β, − 0.3587; p-value, 0.000) or 30-34 years old (β,− 0.38013; p-value, 0.000) were less likely to be mistreated compared to women aged 18 years or younger. Women from a relatively disadvantaged (Dalit) ethnic group were more likely to be mistreated (β, 0.29596; p-value, 0.000) compared to a relatively advantaged (Chettri) ethnic group. Newborns who were born preterm (β, − 0.05988; p-value, 0.000) were less likely to be mistreated than those born at term. Conclusion The study reports high rate of some categories of mistreatment of women during childbirth. Women from disadvantaged ethnic group, young women, and term newborns are at higher risk of mistreatment. Strengthening health system and improving health workers' readiness and response will be key in experience respectful care during childbirth.